Peran Kelompok Rentan Dalam Penanggulangan Bencana dan Pengurangan Resiko Bencana Di Desa Tangguh Bencana (Studi Deskriptif Satuan Tugas Desa Tangguh bencana Di Desa Gunung Geulis, Kecamatan Sukaraja, Kabupaten Bogor - Alifa, Syadza; Wibowo, Arif (UI Scholars Hub, 2015)
This research discusses about the role of vulnerable groups who are being Task Force in disaster management and disaster risk reduction efforts in Gunung Geulis Village, Bogor Region. This study examine the process of formation of the Task Force, the role of vulnerable groups into the Task Force, and the supporting factors and inhibiting factors of the vulnerable groups into the Task Force. This study is a descriptive study with qualitative methods. The methods used are observation, in-depth interviews, and the study of literature. The end results show that the involvement of vulnerable groups as Task Force has been suitable with the regulation, the Task Force from vulnerable groups are active in disaster management and disaster risk reduction efforts, and supporting factors are likely more as long as their needs are accommodated and customize the tasks according to their capacity.